2019
DOI: 10.1080/15140326.2019.1692509
|View full text |Cite
|
Sign up to set email alerts
|

On stock price overreactions: frequency, seasonality and information content

Abstract: This paper explores the frequency of price overreactions in the US stock market by focusing on the Dow Jones Industrial Index over the period 1990-2017. It uses two different methods (static and dynamic) to detect overreactions and then carries out various statistical tests (both parametric and non-parametric) including correlation analysis, augmented Dickey-Fuller tests (ADF), Phillips-Perron (PP) tests, Granger causality tests, and regression analysis with dummy variables. The following hypotheses are tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
2
5
0
1
Order By: Relevance
“…This is confirmed by who showed that the correlation between the frequency of abnormal returns (based on the two aforementioned methods for abnormal returns detection in turn) and the VIX index dynamics is much higher when using the static approach, which is crucial for the purposes of our analysis (i.e. price prediction); 30 specifically, the dynamic trigger approach produces a correlation coefficient of 0.12 whilst the static one yields a coefficient equal to 0.81. Therefore, the static approach will be applied here.…”
Section: Methodssupporting
confidence: 72%
“…This is confirmed by who showed that the correlation between the frequency of abnormal returns (based on the two aforementioned methods for abnormal returns detection in turn) and the VIX index dynamics is much higher when using the static approach, which is crucial for the purposes of our analysis (i.e. price prediction); 30 specifically, the dynamic trigger approach produces a correlation coefficient of 0.12 whilst the static one yields a coefficient equal to 0.81. Therefore, the static approach will be applied here.…”
Section: Methodssupporting
confidence: 72%
“…More recently Kudryavtsev (2013) found evidence of price reversals in the Dow Jones Industrial Index after a day of large high (low) to close prices. Furthermore, Caporale and Plastun (2019a) extended the literature on the US stock market by investigating the frequency of overreactions and found that these were linked to volatility (VIX index). This suggested that overreactions could be used as predictors of market sentiment.…”
Section: Literature Reviewmentioning
confidence: 92%
“…This suggested that overreactions could be used as predictors of market sentiment. No profitable trading opportunities from overreactions where found by Caporale and Plastun (2019a) suggesting market efficiency. Evidence of overreactions were also found by Caporale et al (2019) in the US stock market using weekly data.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Melalui pengujian secara statik dengan menggunakan 2 buah indeks dan beberapa saham blue chips, dibuktikan bahwa overrection terjadi pada pasar modal Ukraina (Plastun et al, 2018). Selain penelitian overreaction secara statik, pembuktian secara statik dan dinamik juga dilakukan untuk meneliti frekuensi harga overreaction dengan statistik parametrik dan non parametrik (Caporale & Plastun, 2019a). Fenomena overreaction juga terjadi pada industri real estate.…”
Section: Pendahuluanunclassified